A case-controlled study of the sexual health needs of lesbians. Issue 4 (August 1996) - Skinner, C J; Stokes, J; Kirlew, Y; Kavanagh, J; Forster, G E
Abstract : OBJECTIVES: To evaluate and compare the range of genital infections diagnosed in a group of lesbians attending an inner city genitourinary clinic with a control group of heterosexual women attending the same clinic. SETTING: The Ambrose King Centre, the Royal London Hospital, a genitourinary clinic within which the Audre Lorde Clinic, a specialist sexual health clinic for women identifying as lesbians, is operated. SUBJECTS: Two hundred and forty one women attending the specialist clinic between October 1993 and September 1994. Heterosexual controls matched for age and ethnicity were selected from the same time period. METHODS: A retrospective case note analysis was made of 241 lesbians and 241 matched heterosexual controls. Data were collected on age, ethnicity, symptoms, diagnoses and services used. RESULTS: An infection was diagnosed in 129 (65%) of the lesbians and 126 (62%) of the heterosexual women. Only 23 (10%) of the lesbians exclusively practised same gender sexual contact. Genital herpes (p = 0.05) and genital warts (p = 0.005) were more common in the heterosexual women. Gonorrhoea and chlamydia infection were infrequent diagnoses in both groups, occurring in four (2%) lesbians and 14 (7%) heterosexuals (p = 0.05). Bacterial vaginosis occurred in 65 (33%) of the lesbians and 27 (13%) of the heterosexuals (p < 0.0001). Cervical cytology abnormalities were uncommon but only found in the lesbians. CONCLUSIONS: Screening for genital infections in lesbians is appropriate. The high prevalence of bacterial vaginosis in this group is unexplained but suggests a possible sexual transmission. Lesbians should be included within the cervical cytology screening programme.